(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Major Construction project in urban India is incorporated with Reinforced Concrete (RC) frames, which experience both static and dynamic forces during their lifetime. Static forces can easily be analysed whereas dynamic force analysis is very time consuming, but it can’t be left unanalysed as the results may be catastrophic. Earthquake is an important dynamic force which a building may experience during its lifespan and is therefore its analysis becomes a critical step in design. The present work in its utmost sense, aim at understanding the influence of different ground motions on the structure over its life span. This providing new parameters and information to help improve design work. INTRODUCTION During an earthquake, the structure undergoes dynamic motion due to reaction of the inertia forces built up in the direction against the acceleration of seismic forces. These inertia forces, also known as seismic forces, are considered by assuming pseudo external forces acting on the building. Excluding gravity loads, predominant structure experiences significant lateral forces of considerable magnitude during seismic action. Thus, before the designing of the structure is carried out, it becomes integral to identify and estimate the magnitude of lateral forces acting on the structure. Reinforced concrete structures are routinely designed for higher strength parameters than the necessary service load constraints. In general, the members are designated with greater dimensions and higher material standards than the minimum strength requirements specified in the IS design codes. The design procedures for seismic loads also results with greater strength parameters. Furthermore, the redundancy of the structure under the account of division of stresses will also lead to increased overall strength. The current study understands the comparison of storey displacement, base shear, and storey drift of RC framed structure with in individual seismic regions of Indian sub-continent.